Moral Judgment Test (MJT) in Urdu: Translation and Validation - Liaquat, Abdul Wahab (ETHICS IN PROGRESS, 2011)
The present study was conducted as part of a larger study that aimed to compare moral judgment competence and moral preferences among Pakistani students of public and private sector educational institutes and religious institutes and also to measure the pattern of development of moral judgment competence of students within these institutes. The validation study completed in two phases, during the 1st phase data were collected from the students of grade 8 to 16 from public sector schools and colleges of Rawalpindi city. Very low mean c-score was observed (M = 13.60, SD = 9.05), the test came out to be valid on preference hierarchy criterion but its validity on the cognitive-affective parallelism and Quasi- simplex structure criteria could not be established due to low c-scores of the sample. In the second phase an additional sample from one private sector and two public sector universities was collected. The analysis of the combined sample (N = 246) showed no significant improvement of c-scores (M = 13.94, SD = 9.53). The test meets well the preference hierarchy criterion but on the other two criteria results remain inconclusive due to low variance in the sample. The low c-scores are explained on the basis of three assumptions; (1) poor quality of education, (2) dogmatic religiosity, and (3) weak and instable political structure of Pakistani society.